Tinjauan Yuridis Pmk No 16 Tahun 2019 Tentang (Kecurangan) Fraud dan Fenomena Pengembalian Uang - Yulita, Fera; Efrilla; Edwin (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Interpretation of the Regulation of the Minister of Health concerning the Prevention of Fraud in National Health Insurance, known by the abbreviation JKN, is a government program that aims to provide access to health services to all levels of society. replacing Permenkes 36/2015 which requires additional evaluation and research. during implementation. there is a risk of fraud In the implementation of JKN which has not yet achieved the expected results, it has also been proven that it has not been monitored by the Fraud Monitoring Group as mandated by Regulation of the Minister of Health No. 16 of 2019. Regarding this, the article further examines Government Regulation No. 16, 2019 and the search for alternative regulatory options To ensure that its implementation can run smoothly. Analyze how to utilize legal provisions, especially statutory provisions. Based on the analysis, it can be concluded that Regulation of the Minister of Health No. 16 of 2019 is still stagnant and there is an opportunity to further optimize the function of the JKN TPF. feasible to be carried out until now, because changes to the Permenkes This process will require a longer time and the necessary tools